FGF-2 enriched nanofiber scaffold for advancing achilles tendon healing: a comparative experimental investigation - Turgut, Necmettin; Cengiz Çallıoğlu, Funda; Bayraktar, Aytül; Savran, Mehtap; Aşcı, Halil; Gülle, Kanat; Ünal, Meriç (Frontiers in Surgery, 2024)
IntroductionAchilles tendon rupture is a common and debilitating injury that significantly impacts mobility and quality of life. Effective treatment options that promote faster and more complete healing are needed. Fibroblast growth factor-2 (FGF-2) has shown potential in enhancing tendon repair. This study aims to investigate the efficacy of FGF-2 in promoting tendon healing in a rat model of Achilles tendon rupture, providing insights into its potential as a therapeutic option.Materials and methodsForty-eight rat hind legs with complete Achilles tendon ruptures were divided into four equal groups: the Sham (S) group (tendon repair only), the Polymer (P) group (tendon repair with scaffold wrapping), the Produced FGF-2 (PF) group (scaffold coated with lab-produced FGF-2), and the Commercial FGF-2 (CF) group (scaffold coated with commercially sourced FGF-2). Histological analyses at two and four weeks post-surgery evaluated healing based on nuclear morphology, vascularity, fibril organization, inflammation, and adipogenesis.ResultsAt the end of the second week, no macroscopic healing was observed in one rat each from the S and P groups. By the end of the fourth week, macroscopic healing was observed in all groups. The S and P groups exhibited similarly severe fibril disorganization, pathological adipogenesis, and sustained inflammation, particularly at the fourth week. In contrast, the CF group demonstrated improved tendon healing with increased vascularity and extracellular matrix, lower inflammatory cell infiltration, and better fibril organization. Pathological adipogenesis was absent in the CF group, especially at the fourth week. The PF group showed comparable improvements at the second week but experienced a relapse by the 4th week, with increased inflammation and adipogenesis.ConclusionFGF-2 coated scaffolds significantly enhanced tendon healing in a rat Achilles tendon rupture model by improving fibril organization, increasing vascularity, and reducing inflammation and pathological adipogenesis. These findings suggest that FGF-2 could be a promising therapeutic option for accelerating tendon repair. Future perspectives on tendon repair will focus on enhancing FGF-2 delivery using innovative scaffolds, paving the way for more effective therapies and improved patient outcomes.